2015
DOI: 10.1177/0033688215595713
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Strategies-based Language Instruction: A Study of Reading Comprehension and Problem Solving Abilities via Structural Equation Modeling

Abstract: The study aimed at exploring the psychological as well as educational outcomes of strategies awareness and use. We set out to examine the effect of reading strategic investment on language achievement and problem solving ability (PSA). The participating EFL learners were heterogeneous in terms of reading instruction; two of the intact groups had received normal instruction studying selected short stories with a primary focus on vocabulary development and comprehension check, whereas the second group had been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 51 publications
5
9
0
Order By: Relevance
“…The same idea is acknowledged by the human development paradigm and humanistic psychology; they hold that education should empower individuals to lead a meaningful and purposeful life through fostering their emotions, relationships, attitudes, thinking styles, and values (Rogers, 1961). Studies like the current one, which have found causal or correlational associations between SBI and different life skills (Chamot et al, 2010;Cheng & Dörnyei, 2007;Ghahari & Basanjideh, 2015Nguyen & Gu, 2013;Tseng et al, 2006), are in line with the view that educational settings, considering their educational environment and the overall purposes they pursue, are the best places for life skills intervention (to use Behura's term) and for developing a fully functioning individual (to use Rogers' term). Of all the language learning practices, one might surmise that learnercentered activities and approaches, such as alternatives in assessment (see Ghahari & Farokhnia, 2017Ghahari & Sedaghat, 2018) and strategies-based instruction, to be more promising when cultivation of learners' positive life-and-learning skills is intended.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The same idea is acknowledged by the human development paradigm and humanistic psychology; they hold that education should empower individuals to lead a meaningful and purposeful life through fostering their emotions, relationships, attitudes, thinking styles, and values (Rogers, 1961). Studies like the current one, which have found causal or correlational associations between SBI and different life skills (Chamot et al, 2010;Cheng & Dörnyei, 2007;Ghahari & Basanjideh, 2015Nguyen & Gu, 2013;Tseng et al, 2006), are in line with the view that educational settings, considering their educational environment and the overall purposes they pursue, are the best places for life skills intervention (to use Behura's term) and for developing a fully functioning individual (to use Rogers' term). Of all the language learning practices, one might surmise that learnercentered activities and approaches, such as alternatives in assessment (see Ghahari & Farokhnia, 2017Ghahari & Sedaghat, 2018) and strategies-based instruction, to be more promising when cultivation of learners' positive life-and-learning skills is intended.…”
Section: Discussionsupporting
confidence: 81%
“…In order to test the students' mastery of reading comprehension and reading strategies, Ghahari and Basanjideh's (2015) test battery with three subsections was adapted. RCTB, the scores for which represented reading comprehension achievement in this study, was basically organized around strategies.…”
Section: Reading Comprehension Test Battery (Rctb)mentioning
confidence: 99%
See 1 more Smart Citation
“…By giving the students more responsibility for learning, language programs encouraged the learners to become more autonomous, to diagnose their own learning strengths and weaknesses, and to self-direct language learning process (Cohen & Weaver, 1998). Moreover, strategy training, if designed carefully and sensitively with the learners' needs in mind, can become a key element in creative and self-directed language learning (Oxford et al, 1990;Ghahari & Basanjideh, 2015, 2017. Therefore, the learners can benefit from coaching in learning strategies and need to become aware of the learning strategies through strategy instruction.…”
Section: Strategies-based Instruction and Its Covariatesmentioning
confidence: 99%
“…The reading exam, the scores of which were considered as reading comprehension achievement in this study, was adopted from Ghahari and Basanjideh (2015). In order to test the students' mastery of reading comprehension and reading strategies, the reading comprehension test battery (henceforth RCTB) had been organized around three subsections.…”
Section: Reading Comprehension Test Batterymentioning
confidence: 99%